Again!! No. 7 - Kubo, Mitsurou, 1975- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2019)
The continuing existence of the ouendan is ensured, now that it's survived its first real field test. But now that Kinichiro's achieved his primary goal, he finds himself at somewhat loose ends, and the prospect of reliving the next three years withall of his foreknowledge brings with it a new set of problems. Meanwhile, Reo's determined to finish what she started with him, one way or another--